All will yet be well : the diary of Sarah Gillespie Huftalen, 1873-1952 - Huftalen, Sarah Gillespie, 1865-1955 (Bur oak original., 1993)
Sarah Gillespie Huftalen led an unconventional life for a rural midwestern woman of her time. Born in 1865 near Manchester, Iowa, she was a farm girl who became a highly regarded country school and college teacher; she married a man older than either of her parents, received a college degree later in life, and was committed to both family and career. A gifted writer, she crafted essays, teacher-training guides, and poetry while continuing to write lengthy, introspective entries in her diary, which spans the years from 1873 to 1952.